2000
DOI: 10.1210/en.141.10.3852
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Estrogen Synthesized by Aromatase P450 in Uterine Leiomyoma Cells Promotes Cell Growth Probably Via an Autocrine/Intracrine Mechanism

Abstract: In the present study we characterized in detail the expression of aromatase P450 in leiomyomas to determine the role of in situ estrogen in the growth advantage of leiomyomas. The levels of aromatase P450 transcripts were determined by quantitative RT-PCR to be significantly higher in leiomyomas than in corresponding myometrium. The overexpression of aromatase P450 in leiomyomas was also confirmed by Western blot analysis. The estimated size of immunoreactive aromatase was 58 kDa, similar to that in placenta. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
0
11

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(125 citation statements)
references
References 0 publications
6
108
0
11
Order By: Relevance
“…The authors speculated that the higher levels of estradiol in the leiomyomas could be related to lower levels of the enzyme 17β-hydroxysteroid dehydrogenase, which accelerates the conversion of estradiol to estrone. Other investigators have also demonstrated higher estradiol concentrations (Folkerd et al 1984) and more frequent expression or overexpression of aromatase activity in leiomyomata than in matched myometrial samples (Folkerd et al 1984;Sumitani et al 2000;Yamamoto et al 1984), leading these authors to entertain the possibility that increased androgen to estrogen conversion in fibroids may potentiate their growth.…”
Section: Laboratory Studiesmentioning
confidence: 99%
“…The authors speculated that the higher levels of estradiol in the leiomyomas could be related to lower levels of the enzyme 17β-hydroxysteroid dehydrogenase, which accelerates the conversion of estradiol to estrone. Other investigators have also demonstrated higher estradiol concentrations (Folkerd et al 1984) and more frequent expression or overexpression of aromatase activity in leiomyomata than in matched myometrial samples (Folkerd et al 1984;Sumitani et al 2000;Yamamoto et al 1984), leading these authors to entertain the possibility that increased androgen to estrogen conversion in fibroids may potentiate their growth.…”
Section: Laboratory Studiesmentioning
confidence: 99%
“…Aromatase mRNA is expressed in myoma but is not expressed in normal myometrial cells [30,31]. Further, estrogen concentration in myoma tissue is greater than in the surrounding myometrium.…”
Section: Aromatase Inhibitorsmentioning
confidence: 93%
“…Some studies have shown that leiomyoma tissues are a source of estrogen. Leiomyoma cells express an estrogen synthetase as well as aromatase and convert circulating androgens to estrogen [30,32,33]. Estrogen secreted by leiomyoma tissue may reach a sufficient concentration within the local compartment to support its own growth, allowing independence from ovarian estrogen [34,35].…”
Section: Aromatase Inhibitorsmentioning
confidence: 99%
“…As compared to the surrounding myometrium, smooth muscle cell myomas contained eleveted levels of aromatase and were able to synthesize estrogen [10,11] while tissue concentrations of estrogen were augmented in smooth muscle cell myomas as compared to the surrounding myometrium [12,13]. In addition, in vitro experiments proved that estrogen synthesized in smooth muscle cells in a culture was sufficient to support proliferation in an intracrine manner, since stimulation of aromatase activity increased cell proliferation while an aromatase inhibitor reduced the proliferation [11].…”
Section: Introductionmentioning
confidence: 99%